DEVELOPMENT OF MATHEMATICS MODULE WITH STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) BASED ON SCIENTIFIC APPROACH IN SET MATERIAL FOR GRADE VII STUDENTS OF SMP / MTS - Azzahrotul Jannah; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
Teaching materials are seen as fundamental instruments in the learning process and limited teaching materials with Curriculum 2013—modules and package books available, limited, and not easily understood by students. The mathematics module is one of the alternative teaching materials that can facilitate teachers and improve student ability. This development research aims to develop teaching materials in the form of Mathematics Module Set with Student Teams Achievement Divisions (STAD) Based Scientific Approach for Grade VII Students of Junior High School (SMP/MTs) and test the quality (feasibility) of the module. This development research uses Research and Development (R & D) method. Research subjects include material experts, media experts, students of two schools. Data collection techniques used were interviews, questionnaires. The research instruments are questionnaires that have been reviewed. The data analysis technique is done qualitatively and quantitatively to calculate the learning module's feasibility test result. The results of the material feasibility test are included in either criterion with an average score of 67. The module media feasibility test is included in either criterion with an average score of 67.67. Simultaneously, the result of the questionnaire of student response of small grade product trial stage included good criterion with an average score of 64,7. The results of the material experts with an excellent category with an average score of 79.67, in terms of media experts with a very good category with an average score of 74.33, the results of questionnaires student response test phase of large class products including very good criteria with an average score of 71.5. The results show that the mathematics module of the set matter with the STAD method based on the scientific approach for the students of grade VII SMP / MTs is feasible for the learning process.